The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/anie.202209004
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Oxidative Lactonization of Enynyl Boronates

Abstract: Oxidation of CÀ B bonds is extensively used in organic synthesis, materials science, and chemically biology. However, these oxidations are usually limited to the oxidation of C(sp 3 )À B and C(sp 2 )À B bonds. The C(sp)À B bond oxidation is rarely developed. Herein we present a novel strategy for the preparation of γ-lactones via the oxidation of enynyl boronates. This process successively involves the C(sp)À B bond oxidation, the epoxidation of CÀ C double bond and the lactonization. This protocol provided va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…The PL spectra of the doped films were slightly red‐shifted and a slight broadening of FWHM was observed compared to those in toluene (Figure S14), due to the solid solvation effect of the host material and the aggregation effect of the dopant [38] . Such interaction is more obvious in ODBN doped films, which exhibit larger broadening of the emission profile with the increase of doping concentration (Figure S14), probably due to the more planar configuration for shortening the intermolecular distance [48, 49] . Moreover, the PLQYs of the doped films were tested, being 50 %, 71 % and 86 % for OBN , NBN and ODBN (Figure 2c), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The PL spectra of the doped films were slightly red‐shifted and a slight broadening of FWHM was observed compared to those in toluene (Figure S14), due to the solid solvation effect of the host material and the aggregation effect of the dopant [38] . Such interaction is more obvious in ODBN doped films, which exhibit larger broadening of the emission profile with the increase of doping concentration (Figure S14), probably due to the more planar configuration for shortening the intermolecular distance [48, 49] . Moreover, the PLQYs of the doped films were tested, being 50 %, 71 % and 86 % for OBN , NBN and ODBN (Figure 2c), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with QAO , hp -BQAO possesses a smaller Δ E ST but a longer τ d , which is probably attributed to the less affected triplet states of the twisted MR-emitters by the surroundings. 13 As for pe -QAO , [5] he -BQAO and [6] he -BQAO that possess large Δ E ST , only short-lived prompt fluorescence was observed, indicating the absence of TADF nature. In addition, the pe -QAO -doped film reveals a broadband spectrum (FWHM = 79 nm) with a low PLQY of 39% because of its planar configuration.…”
Section: Resultsmentioning
confidence: 99%
“…57 Such modifications enhanced the molecule's rigidity while inhibiting intermolecular interactions, ultimately leading to only a 1.8% drop in efficiency at 100 cd m −2 for the BN-DPAC-based device. Duan et al and Yang et al reported D-Cz-BN 58 and BN-CP1 59 (Fig. 8), respectively, which were sterically wrapped by bulk substituents.…”
Section: Boron-based Mr-tadf Emittersmentioning
confidence: 94%